Indigenas, quilombolas e dendeicultura na Amazônia: expropriações e relações de poder no Alto do Vale do rio Acará no município de Acará/PA (1980-2021) - SAAVEDRA, Maria da Paz Corrêa (Universidade Federal do Pará, 2025)
In the Amazon, in the rural area of the Pará, territories are appropriated for the interests of big capital without identification with the surroundings in which they are established, configuring the growth of territorial insecurity due to large enterprises, culminating in enclosures, the core of the expropriation of traditional communities, making explicit challenges to the institutionalization of ethnic recognition contemplated in normative instruments and, contributing to the permanence of the historical process of invisibilization of populations that claim territorial rights. In this work, using oral memory as the main element of the methodology, the aim is to seek, present and endorse the daily struggles, fields of action, resistance and experiences as well as the political struggle that currently self-identified quilombola and indigenous families experience when narrate the usurpation of their territories and the conflict situations triggered by the oil palm farming activities of the company Agropalma S. A., in the Vale do Alto Rio Acará, in the municipality of Acará/PA. Historical evidence and narratives built around ethnic belonging indicate the constitution of specific territorialities, indicators of a collective existence. Oral records use memory to detail facts that imprint material and symbolic forms on the territory, tracing a close relationship between memory, territory and identity, since strong images of places are recorded in these. Even though they present themselves in the present, all these questions are deeply historical and aim to contribute to the studies of regional historiography, in particular, studies on original peoples in the state of Pará.